In situ growth of urchin-like NiCo2S4 hexagonal pyramid microstructures on 3D graphene nickel foam for enhanced performance of supercapacitors. Issue 12 (25th January 2016) - Wang, Xiaoli; Xia, Xianjun; Beka, Lemu Girma; Liu, Weihua; Li, Xin
Abstract : Urchin-like NiCo2 S4 hexagonal pyramid microstructures have been successfully fabricated on 3-D graphene nickel foam by a two-step hydrothermal method. These achieve a rather high mass loading, with enhanced specific capacitance, rate performance and cycling stability. Abstract : Urchin-like NiCo2 S4 hexagonal pyramid microstructures have been grown in situ on three dimensional (3D) graphene nickel foam (GNF) by two-step hydrothermal method, labeled as NCS-GNF. The presence of graphene between nickel cobalt sulphur (NCS) and nickel foam (NF) can effectively improve ion and charge transportation. As a binder-free electrode for supercapacitors, it exhibits an ultrahigh specific capacitance of 9.6 F cm −2 at 10 mA cm −2 with excellent rate performance and cycling stability at a mass loading of 5.8 mg cm −2, corresponding to a mass specific capacitance of about 1650 F g −1 at 1.7 A g −1 . The excellent electrochemical performance of urchin-like NCS-GNF is attributed to its unique microstructure. This unique microstructure electrode material has a promising application for capacitors in future.